(untitled) (Huellas, 2018)
Contemporary changes in the political, social, scientific and technological fields have changed the meaning of school education, of the Social Sciences in general and of Geography and History in particular. Within these changes, the curricular materials in La Pampa incorporate political, economic, social, environmental and territorial issues into the teaching areas, and also decide on which scales of analysis to use for their understanding. The Geographic Information Technologies (GIT) are a powerful tool for classroom work on these dimensions, thus favoring the production and cartographic interpretation. The main objectives of this work involve raising awareness among teachers of ongoing training tools in order for them to acquire the new technologies, and to implement teaching proposals from the generation and implementation of problem situations that allow students to understand the geographical space as a process of social construction subject to continuous changes, and to multiple and complex relationships. Also, to reflect on the close relationship between autonomous learning by discovery and the use of GITs.